Pola Sosialisasi Nilai Ajaran Agama dan Budi Pekerti Berbasis Akulturasi Budaya Pada Seni Selawatan Gembrung - Kurnianto, Rido (UIN Maliki Malang, 2012)
This research focused on the strategic aspect to cultural acculturation in the artof selawatan gembrung wich existed in the community and formed a culturalsystem of moral values. As a valuable art, the existence of selawatan gembrungis still needed in Ponorogo, Madiun, Ngawi, Magetan, Pacitan, and TrenggalekRegency to counter the individualism as the influence of globalization. Thisidentification will formulize the socialization pattern of religious and goodcharacter values in cultural acculturation within developing community andwill be useful for writing a module as a reference for better understanding,comprehension, and implementation of religious and good character values.This study is qualitative research based on sociology of religion approuch which tries to reveal the harmonization between religion doctrine and tradition or culture in community that is well known as acculturation in anthropologyand sociology. This study found the aspects of acculturation on text, costume,gamelan instruments, and stage ritual of selawatan gembrung. Those aspectshave reformed this traditional kind of art into the well-being existence of